2016
DOI: 10.1186/s12934-016-0580-x
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of the sugar sensing in Saccharomyces cerevisiae indicates endogenous mechanisms for xylose signaling

Abstract: BackgroundThe sugar sensing and carbon catabolite repression in Baker’s yeast Saccharomyces cerevisiae is governed by three major signaling pathways that connect carbon source recognition with transcriptional regulation. Here we present a screening method based on a non-invasive in vivo reporter system for real-time, single-cell screening of the sugar signaling state in S. cerevisiae in response to changing carbon conditions, with a main focus on the response to glucose and xylose.ResultsThe artificial reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 83 publications
5
32
0
Order By: Relevance
“…Glucose induces the Crabtree effect in S. cerevisiae (Diaz‐Ruiz, Rigoulet, & Devin, ) and is known to repress mitochondria biogenesis compared with nonfermentative carbon sources such as glycerol (Egner et al, ). In contrast, xylose is not recognized as a fermentable carbon source and induces a respiratory response in yeast engineered to consume it (Belinchón & Gancedo, ; Brink, Borgström, Tueros, & Gorwa‐Grauslund, ; Jin et al, ; Osiro, Borgström, Brink, Fjölnisdóttir, & Gorwa‐Grauslund, ; Osiro et al, ). Considering that the isobutanol production pathway in SR8‐Iso is compartmentalized in the mitochondria, it is likely that increased mitochondrial biogenesis is a major contributor to the enhanced isobutanol yields from xylose we observe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose induces the Crabtree effect in S. cerevisiae (Diaz‐Ruiz, Rigoulet, & Devin, ) and is known to repress mitochondria biogenesis compared with nonfermentative carbon sources such as glycerol (Egner et al, ). In contrast, xylose is not recognized as a fermentable carbon source and induces a respiratory response in yeast engineered to consume it (Belinchón & Gancedo, ; Brink, Borgström, Tueros, & Gorwa‐Grauslund, ; Jin et al, ; Osiro, Borgström, Brink, Fjölnisdóttir, & Gorwa‐Grauslund, ; Osiro et al, ). Considering that the isobutanol production pathway in SR8‐Iso is compartmentalized in the mitochondria, it is likely that increased mitochondrial biogenesis is a major contributor to the enhanced isobutanol yields from xylose we observe.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose induces the Crabtree effect in S. cerevisiae (Diaz-Ruiz, Rigoulet, & Devin, 2011) and is known to repress mitochondria biogenesis compared with nonfermentative carbon sources such as glycerol (Egner et al, 2002). In contrast, xylose is not recognized as a fermentable carbon source and induces a respiratory response in yeast engineered to consume it (Belinchón & Gancedo, 2003;Brink, Borgström, Tueros, & Gorwa-Grauslund, 2016;Jin et al, 2004;Osiro, Borgström, Brink, Fjölnisdóttir, & Gorwa-Grauslund, 2019;Osiro et al, 2018).…”
mentioning
confidence: 99%
“…5). Lastly, as extracellular xylose cannot sufficiently interact with Snf1p [134], a sensor protein that downregulates the expression of ACC1 and upregulates β-oxidation [133], xylose culture could prevent inhibition of fatty acid synthesis and degradation of acyl-CoA.
Fig. 5Schematic comparison between glucose ( orange ) and xylose ( blue ) metabolisms in engineered S. cerevisiae .
…”
Section: Production Of Advanced Biofuels and Chemicals From Xylose Bymentioning
confidence: 99%
“…Recently, the Gorwa‐Grauslund lab conducted several studies on xylose‐sensing. They assessed the effect of xylose when GFP was expressed under various promoters in strains that can or cannot metabolize xylose . Their results demonstrated that extracellular xylose was not detected by S. cerevisiae .…”
Section: Engineering Xylose Metabolismmentioning
confidence: 99%